ZAKAT UNTUK SEKTOR PRODUKTIF: STUDI PADA ORGANISASI PENGELOLA ZAKAT DI SURAKARTA - Muh Juan Suam Toro; Hasim Hasim; M Amien Gunadi; Indah Piliyanti (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2013)
This paper is part of research that aims to investigate whether Organisasi Pengelola Zakat (OPZ) or Zakat Management Organisations in Surakarta have the awareness to distribute zakat fund to the productive sector and to address the contribution that has been made in this sector by OPZ. This study also investigated the constraints faced by OPZ in distributing zakat to the productive sector. Using explorative approach, this study uses two stages of data collection. Results showed that the first stage, OPZ generally already have the awareness to channel to the productive sectors of the economy. Four OPZ as an informant in the second stage with in-depth interviews showed that each organization has a unique program in distributing zakat fund to the productive sector. The constraints of distribution to productive economic sectors are focus on institutions, inavailability of good distribution systems, and the lack of skilled human resource.